Intercultural approach on photoprotection and skin cancer prevention in nursing students - Carla Cristina Calderón Cabezas; Angélica Salomé Herrera Molina; Yolanda Elizabeth Salazar Granizo; Jimena Alexandra Morales Guaraca; Paola Maricela Machado Herrera; Jacobo Cambil Martín (Medisur)
Foundation: skin cancer as a public health problem requires facing it through comprehensive, transversal and sustainable prevention strategies, based on the reality of the individual, family and community; where previous experiences, beliefs and customs are included, taking into account cultural diversity. Objective: determine the intercultural practice of photoprotection in nursing students at the Chimborazo National University for the skin cancer prevention. Methods: research with a qualitative-interpretive approach, considering narrative and experiential data supported for the in-depth description of the phenomenon. The studied subjects constituted 12 key informants who met the inclusion criteria. The data were collected through semi-structured interviews and self-reporting. The interviews were transcribed, categorized, interpreted and triangulated. Results: the intercultural practice of photoprotection in nursing students was related to three central categories: culture/health with cultural photoprotection care; environment with worldview and cultural environment; and promotion with learning and/or education needs on photoprotection respectively. Categories that are supported by the rising sun model proposed by Madeleine Leininger. Conclusions: Leininger's theory directs students and health professionals to be aware of cultural attitudes and work in collaboration with users, providing promotion and prevention strategies that are culturally appropriate and effective, where factors such as language, traditions and cultural norms are taking into account.